RANAH JIHAD PEREMPUAN DALAM PERSPEKTIF HADIS - St. Jamilah Amin (LPPM IAIN Parepare, 2016)
Status of jihad in Islam is parallel to belief in God, even some scholars jugde jihad as one of the pillars of faith. With such a position, jihad movement attracts all Muslims both men and women. Even in the name of jihad, persons do violence or terror to other groups who are not the same faith with them. This attitude is motivated by a less precise interpretation to the concept of jihad in Islam, that jihad is a physical war. If jihad is interpreted as physical war, so only man who could take a part in jihad, whereas women do not. In fact, when a female “shabahah” asked Muhammad SAW to get involved in a war led by him, then the prophet replied that women’s jihad is in her household, take care of children and serve her husband. This article will strengthen out the true meaning of jihad.